The Effort Of Improving The Quality Of Employee’s Performance (Studi On Sosgul Malang) - Zaim Mukaffi; Pipin Setyo Utomo (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2020)
This study aims to determine the effort of improving the quality of employee’s performance at CV Cucurutuku Ceria Sosgul Malang. The research approach used a qualitative method where the informants in this study were the employees of the sales counter, Coordinators and HR of CV Cucurutuku Ceria Sosgul Malang who are the planner of the improvement program and targets. The Data collection was carried out through interviews, observation, documentation and field data collection. The data analysis techniques use descriptive analysis, such as: data reduction, data presentation and conclusions. The results of this study indicate that the efforts made by CV Cucurutuku Ceria Sosgul Malang to improve the quality of employee’s performance show: 1) through training or programmatic training related to technical matters such as: how to produce, service sales transactions and financial reporting. 2) Conducting employee discipline development such as: discipline for work attendance, services, and working hours. These are contained in standard operational procedures (SOPs) written in company’s regulations.